Epidemiological aspects of head and neck cancers in a population of south east region of Iran - Hamideh Kadeh; Shirin Saravani; Babak Moradbeiki (Babol University of Medical Sciences, 2015)
Introduction: The geographical distribution of head and neck cancer shows considerable variation and it is site dependent. The review of the literature shows few data concerning the head and neck cancer patterns in Iran. The purpose of this study was to represent epidemiological aspects of head and neck cancers in south east of Iran. Materials &Methods: In this retrospective study, from a total of 924 diagnosed patients with cancer in the pathology department of dentistry school archives and two main hospitals in south east of Iran during 2006-2012, 287 cases of head and neck cancer were diagnosed histopathologically . Demographic data of patients such as age, gender, location and type of cancer (carcinoma, sarcoma, melanoma, metastatic, or primary) were obtained from patients’ records. Data were analyzed by SPSS statistical software (V.21) using the chi-square test. Results: Squamous cell carcinoma (39.7%) and basal cell carcinoma (26.8%) were the most common malignancies in the head and neck region. The mean age of the patients was 56.1±12.8 years and the relationship between age groups and head and neck cancers was not statistically significant (P=0.085). Male to female ratio was 0.9 to 1. The relationship between gender and types of head and neck cancers was not statistically significant.(P=0.114) Conclusion: In this study, prevalence of head and neck cancer in south east of Iran (Zahedan) was relatively high. However, comparison between findings of our study with other studies shows a relation consistency.